Na co odpowiada deregulacja? Inflacja prawa a nadregulacja - Wróblewski, Bartłomiej (PRAWO i WIĘŹ, 2026)
Polan‘’s accession to the European Union triggered an intense wave of debate concerning the phenomenon of legal inflation. Various diagnoses of the problem were soon followed by proposed remedies. In legal theory and legislative studies, these remedies were primarily linked to the conviction that the law-making process itself required substantial improvement. In public discourse, however, hope was predominantly placed on deregulation. Nevertheless, both the conceptual contours of "deregulation” and the very notion of legal inflation have remained remarkably vague and blurred in most of these discussions.  The purpose of this paper is to examine the issue of “deregulation” not from the perspective of the legislative process or its constitutional dimension, but rather by focusing on the object of deregulation — that is, the phenomenon (or set of phenomena) variously described as “legal inflation,” “over-regulation,” and numerous other terms. The paper defines the concepts of legal inflation sensu stricto and sensu largissimo, and also indicates the possibility of defining legal inflation sensu largo. The core concept – legal inflation sensu stricto – encompasses not only cases of “excessive regulation” but also, and crucially, a decline in the quality of law. It refers to the enactment of provisions that are non-normative (i.e. that do not express legal norms or fragments necessary for their interpretation, or do so in a defective manner), including so-called duplicate rules, widow rules, orphan rules, and poorly drafted provisions, as well as law that is unclear, incoherent, or ineffective.